(untitled) (GEOmedia, 2009)
10th meeting of GRASS & GFOSS users The 10th Italian Congress of GRASS GIS and Geospatial Free and Open Source Software (GFOSS) was held on the26 and 27 Feb in Cagliari. Highlights included updates on major GFOSS projects (GRASS, QGIS), the presentation of new projects (SpatiaLite) and the public release of a free 3D visualization application suitable for distribution over the internet (RATMAN). Many users and developers connected to forge new business relationships and share new ideas.